A study on axial cracking failure of drill pipe body. (January 2016) - Liu, Yonggang; Lian, Zhanghua; Lin, Tiejun; Shen, Youdong; Zhang, Qiang
Abstract: Frequently happening drill pipe failure accidents in oil and gas wells not only affect drilling speed, but cause enormous economic losses and many safety issues. Most of these accidents are transverse cracking of drill pipe body and pin thread or axial cracking of box thread. Based on the axial cracking failures of drill pipe body in an ultra-deep well in China, this paper give a systematic analysis of axial cracking failure in consideration of service condition, material quality and stress corrosion mechanism. Measurement and inspection are performed on macroscopic and microscopic morphology of crack surface, corrosion products and circumferential residual stress. Then stress corrosion cracking experiments against hydrogen sulfide is conducted. Finally, the critical stress value for sulfide stress corrosion cracking of the drill pipe material is obtained, and the mechanisms of axial cracking failure and corresponding preventive measures are proposed. Highlights: Drill pipe with axial cracks was studied with magnetic powder inspection and SEM. The mechanics properties of failed drill pipe were experimentally analyzed. Material structure and crack morphology were analyzed. The SSCC test was conducted to obtain the critical stress value of SSCC. The reasons and mechanisms of axial cracking were studied.